Dampak Kualitas Produk, Citra Merek dan Harga Terhadap Keputusan Pembelian Honda Brio di Surabaya - Malik Hidayatullah; Achmad Daengs GS; Rina Dewi; Bambang Karnain; Harsono Teguh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
The aim of this research is to determine the influence of product quality, brand image and price on the decision to purchase a Honda Brio car in Surabaya. This research was conducted using a quantitative approach. The data for this research is a sample of 96 respondents whose sampling used Roa Purba. The data collection method is a questionnaire. The data analysis used in this research is multiple linear regression analysis with SPSS 26 software. Data that meets the validity test, reliability test and classical assumption test is processed to produce the regression equation: Y = 4.573 + 0.219 X1+ 0.597X2 + 0.638X3 + e. The results of the analysis carried out can be seen through the results of the t test. It can be seen that the variables product quality, brand image and price partially have a significant influence on the decision to purchase a Honda Brio car in Surabaya with each having a calculated t value (2.077), t calculated (5,967). and t count (4.511) which is greater than t table (1.66088). The results of the F test in this research show that the calculated F value (46.662) is greater than the F table (3.09), which means that the variables of product quality, brand image and price simultaneously have a significant influence on the decision to purchase a Honda Brio car in Surabaya.